2015
DOI: 10.1093/jxb/erv116
|View full text |Cite
|
Sign up to set email alerts
|

Planteose as a storage carbohydrate required for early stage of germination of Orobanche minor and its metabolism as a possible target for selective control

Abstract: HighlightPlanteose metabolism was uncovered as a key metabolic pathway for germination of Orobanche minor. Inhibition of planteose metabolism by nojirimycin resulted in selective inhibition of O. minor germination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 54 publications
(55 reference statements)
4
63
0
Order By: Relevance
“…It also showed that removing soluble starch from the growth medium did not affect NJ production. Table 1 7) If S. ficellus cultures could be stored for a long duration without any treatment, such as sulfite adduction, and still exhibit inhibitory activity, costs might be further reduced. This study, therefore, also evaluated NJ stability and inhibitory activity against the seed germination of parasitic weeds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It also showed that removing soluble starch from the growth medium did not affect NJ production. Table 1 7) If S. ficellus cultures could be stored for a long duration without any treatment, such as sulfite adduction, and still exhibit inhibitory activity, costs might be further reduced. This study, therefore, also evaluated NJ stability and inhibitory activity against the seed germination of parasitic weeds.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of radicle elongation was also observed upon treatment with an NJ standard. 7) Parasitic weeds cannot survive unless they parasitize host plants immediately after germination; thus, the inhibition of radicle elongation represents a promising method of controlling parasitic weeds. The components in CMB except for NJ would not contribute to these inhibitory activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, a downstream product of sucrose, α-D-glucose-1P, was hydrolysed to α-D-glucose-6P under the action of two upregulated genes, namely, PGM2 (TRINITY_DN79669_c0_g2) and PGM (TRINITY_DN72581_c0_g6), in hulled seeds, but the expression of these genes was very low expression in de-hulled seeds; these genes encode phosphoglucomutase and are further involved in the glycolysis pathway. It has been reported that sucrose may be an intermediate of plant metabolism, and the decrease in sucrose decomposition results in low levels of glucose and fructose and inhibits seed germination [32].…”
Section: Genes and Metabolites In Starch And Sucrose Metabolic Pathwamentioning
confidence: 99%